Dual Targeting of Histone Methyltransferase G9a and DNA‐Methyltransferase 1 for the Treatment of Experimental Hepatocellular Carcinoma. Issue 2 (4th January 2019) - Bárcena‐Varela, Marina; Caruso, Stefano; Llerena, Susana; Álvarez‐Sola, Gloria; Uriarte, Iker; Latasa, M. Ujue; Urtasun, Raquel; Rebouissou, Sandra; Alvarez, Laura; Jimenez, Maddalen; Santamaría, Eva; Rodriguez‐Ortigosa, Carlos; et al.
Abstract: Epigenetic modifications such as DNA and histone methylation functionally cooperate in fostering tumor growth, including that of hepatocellular carcinoma (HCC). Pharmacological targeting of these mechanisms may open new therapeutic avenues. We aimed to determine the therapeutic efficacy and potential mechanism of action of our dual G9a histone‐methyltransferase and DNA‐methyltransferase 1 (DNMT1) inhibitor in human HCC cells and their crosstalk with fibrogenic cells. The expression of G9a and DNMT1, along with that of their molecular adaptor ubiquitin‐like with PHD and RING finger domains‐1 ( UHRF1 ), was measured in human HCCs (n = 268), peritumoral tissues (n = 154), and HCC cell lines (n = 32). We evaluated the effect of individual and combined inhibition of G9a and DNMT1 on HCC cell growth by pharmacological and genetic approaches. The activity of our lead compound, CM‐272, was examined in HCC cells under normoxia and hypoxia, human hepatic stellate cells and LX2 cells, and xenograft tumors formed by HCC or combined HCC+LX2 cells. We found a significant and correlative overexpression of G9a, DNMT1, and UHRF1 in HCCs in association with poor prognosis. Independent G9a and DNMT1 pharmacological targeting synergistically inhibited HCC cell growth. CM‐272 potently reduced HCC and LX2 cells proliferation and quelled tumor growth, particularly in HCC+LX2 xenografts. Mechanistically, CM‐272 inhibited the metabolic adaptation of HCC cells to hypoxia and induced a differentiated phenotype in HCC and fibrogenic cells. The expression of the metabolic tumor suppressor gene fructose‐1, 6‐bisphosphatase ( FBP1 ), epigenetically repressed in HCC, was restored by CM‐272. Conclusion: Combined targeting of G9a/DNMT1 with compounds such as CM‐272 is a promising strategy for HCC treatment. Our findings also underscore the potential of differentiation therapy in HCC.